The Leveraging Effect of Supervisory Competencies Towards the Performance in Indian Manufacturing Group: A Structural Equation Modelling Approach. (1st September 2016) - Vijayabanu, C.; Therasa, C.
Abstract : The quick pace of technological changes, market and industry changes, demographic composition change and society changes requires that human resource managers should revitalize their proficiencies to go with these new challenges. The manager who is a liaison in the organizational hierarchy does a very important job in the organization to direct and channel the employee cluster towards its organization goal, and ensure that each member of the team should be dynamic and prolific. The study on supervisory competency analysis is a crucial and fundamental requirement for any organization. The current study 'The leveraging effect of Supervisory competencies towards the performance in Indian manufacturing group' is based on primary data collected from one hundred and fifty employees working in a paper manufacturing industry. The data collected were analysed using SPSS and SMART PLS software. The results of the study revealed that the impact of supervisory competencies towards his performance is huge which accounts to 81% ( R 2 = 0.810) and towards the growth of whole organization is 35% ( R 2 = 0.356). This implies that if the supervisory level employees are competent enough by possessing certain competencies, his individual performance will do extreme wonders and will create a strong bond between him and the organization and also create an impact on organization growth by clear strategy formulation, creating committed workforce, developing the organization as learning organization and stimulating individual and group productivity.